How can we presume a kid is having risk factors for cardiovascular disease? - Fernando Aguirre Palacios; Gregory Celis (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Digital health has come into reality, thanks to the new technologies such as Artificial Intelligence and Deep learning, contributing in a transcendental way to advances in the prevention, diagnosis, treatment and monitoring of diseases; In addition, this occurs at a crucial moment, marked by the growing prevalence of chronic diseases and the increase in life expectancy. In this context, digital health is not only necessary but, according to experts, it is the key to guaranteeing the present and future of quality healthcare.